Potensi Dan Pengembangan Daya Tarik Wisata Rumah Semut (Musamus) Di Kabupaten Merauke - Reni Sulistiyowati; Nicko Gana Saputra; Dewi Fitriani (Jurnal Sains Terapan Pariwisata, 2021)
Indonesia is an archipelagic country that has a variety of natural, ethnic and cultural beauties. This diversity makes a lot of tourism potential, both natural and cultural, which is able to attract the interest of many local and foreign tourists. Indonesia has a lot of potential and natural resources that have not been developed optimally, including in the tourism sector. One of the tourism sectors that want to be developed is the ant house (Musamus) as a local tourist attraction in the city of Merauke. This study aims to find out how the development strategy will be carried out to increase the potential of the ant house as a local tourist attraction in Merauke Regency. This study uses with a qualitative approach, through a research design to describe and analyze the development of tourism potential in Merauke Regency which is not yet optimal.